Acquittal of Gotovina and Markač: A Blow to the Serbian and Croatian Reconciliation Process - Radmila Nakarada (Merkourios, 2013)
On 16 November 2012, the Appeals Chamber of the International Criminal Tribunal for the former Yugoslavia ('ICTY') issued its decision on Prosecutor v Gotovina et al. The de novo review found errors in the Trial Chamber's analysis and the appellants Gotovina and Markač were acquitted of all charges. This decision has made an impact on the Serbian-Croatian reconciliation process, creating a gap between the two States' historical narratives. Highlighting the arguments in the dissenting opinions, this case note discusses the '200 Metre Standard' and the treatment of modes of liability in the alternative. Furthermore, the reception of the Appeals Judgement by Serbia and Croatia is discussed to demonstrate the political and social consequences of the decision.